The role of long non-coding RNA NORAD in digestive system tumors - Yussel Pérez-Navarro; Yarely M. Salinas-Vera; Cesar López-Camarillo; Elisa Elvira Figueroa-Angulo; María Elizbeth Alvarez-Sánchez (Non-coding RNA Research)
In recent years, it has been discovered that the expression of long non-coding RNAs is highly deregulated in several types of cancer and contributes to its progression and development. Recently, it has been described that in tumors of the digestive system, such as colorectal cancer, pancreatic cancer, and gastric cancer, DNA damage-activated lncRNA (NORAD) was frequently up-regulated. The purpose of this review is to elucidate the functions of NORAD in tumors of the digestive system, emphasizing its involvement in important cellular processes such as invasion, metastasis, proliferation, and apoptosis. NORAD acts as a ceRNA (competitive endogenous RNA) that sponges microRNAs and regulates the expression of target genes involved in tumorigenesis. Thus, the mechanisms underlying the effects of NORAD are complex and involve multiple signaling pathways. This review consolidates current knowledge on the role of NORAD in digestive cancers and highlights the need for further research to explore its potential as a therapeutic target. Understanding the intricate functions of NORAD could elucidate the way for innovative approaches to cancer treatment.